Maud JL Graff. Effectiveness and efficiency of community based occupational therapy for older people with dementia and their caregivers - Netta van 't Leven; Maud J. L. Graff; M. Vernooij-Dassen; Marcel G. M. Olde Rikkert (Tijdschrift voor Gerontologie en Geriatrie, 2008)
bespreking proefschrift